Genistein protects against Aβ25–35 induced apoptosis of PC12 cells through JNK signaling and modulation of Bcl-2 family messengers. Issue 1 (December 2017) - You, Fuling; Li, Qiao; Jin, Guifang; Zheng, Yaojie; Chen, Jingrong; Yang, Hong
Abstract Background Deposition of aggregated amyloid beta (Aβ) protein is hallmark of Alzheimer's disease, leading to dysfunction and apoptosis of neurons. The isoflavone phytoestrogen compound genistein (Gen) exerts a significant protective effect against Aβ25–35 induced neurotoxicity and mitochondrial damage in rat pheochromocytoma (PC12) cells. However, the mechanisms underlying Gen's rescue remain elusive. Therefore we endeavored to research further the molecular mechanisms underlying Gen's inhibition of Aβ25–35 induced apoptosis of neurons. Results We found that Gen dramatically suppressed the activation by Aβ25–35 of p-c-Jun N-terminal kinase (p-JNK), and also inhibited the JNK-dependent decreased of Bcl-w and increased of Bim. Furthermore, Gen significantly reduced the cytoplasmic concentrations of cytochrome c and Smac protein as well as caspase-3 activity. Additionally, pretreatment with JNK inhibitor SP600125 effectively suppressed Aβ25–35 induced PC12 cell cytotoxicity. Conclusion Taken together, the results suggested that Gen protects PC12 cells from Aβ25–35 induced neurotoxicity by interfering with p-JNK activation, thus attenuating the JNK-dependent apoptosis through the mitochondrial pathway. These findings constitute novel insights into the pathway for Aβ25–35 toxicity, and the neuroprotective action of Gen.